Genomic and Chemical Diversity in Cannabis. (1st November 2016) - Lynch, Ryan C.; Vergara, Daniela; Tittes, Silas; White, Kristin; Schwartz, C. J.; Gibbs, Matthew J.; Ruthenburg, Travis C.; deCesare, Kymron; Land, Donald P.; Kane, Nolan C.
ABSTRACT: Plants of the Cannabis genus are the only prolific producers of phytocannabinoids, compounds that strongly interact with the evolutionarily ancient endocannabinoid receptors shared by most bilaterian taxa. For millennia, the plant has been cultivated not only for these compounds, but also for food, rope, paper, and clothing. Today, specialized varieties yielding high-quality textile fibers, nutritional seed oil, or high cannabinoid content are cultivated across the globe. However, the genetic identities and histories of these diverse populations remain largely obscured. We analyzed the nuclear genomic diversity among 340 Cannabis varieties, including fiber and seed oil hemp, high cannabinoid drug-types, and feral populations. These analyses demonstrate the existence of at least three major groups of diversity with European hemp varieties more closely related to narrow leaflet drug-types (NLDTs) than to broad leaflet drug-types (BLDTs). The BLDT group appears to encompass less diversity than the NLDT, which reflects the larger geographic range of NLDTs, and suggests a more recent origin of domestication of the BLDTs. As well as being genetically distinct, hemp, NLDT, and BLDT genetic groups produce unique cannabinoid and terpenoid content profiles. This combined analysis of population genomic and trait variation informs our understanding of the potential uses of different genetic variants for medicine and agriculture, providing valuable insights and tools for a rapidly emerging valuable industry.